Vagus nerve stimulation: Surgical technique of implantation and revision and related morbidity. (April 2017) - Giordano, Flavio; Zicca, Anna; Barba, Carmen; Guerrini, Renzo; Genitori, Lorenzo
Summary: Indications for vagus nerve stimulation (VNS) therapy include focal, multifocal epilepsy, drop attacks (tonic/atonic seizures), Lennox‐Gastaut syndrome, tuberous sclerosis complex (TSC)–related multifocal epilepsy, and unsuccessful resective surgery. Surgical outcome is about 50–60% for seizures control, and may also improve mood, cognition, and memory. On this basis, VNS has also been proposed for the treatment of major depression and Alzheimer's' disease. The vagus nerve stimulator must be implanted with blunt technique on the left side to avoid cardiac side effects through the classic approach for anterior cervical discectomy. The actual device is composed of a wire with three helical contacts (two active contacts, one anchoring) and a one‐pin battery. VNS is usually started 2 weeks after implantation with recommended settings of stimulation (1.0–2.0 mA; 500 μs pulse width; 20–30 Hz; 30 s ON, 5 min OFF). The complications of VNS therapy are early (related to surgery) and late (related to the device and to stimulation of the vagus nerve). Early complications include the following: intraoperative bradycardia and asystole during lead impedance testing, peritracheal hematoma, infections (3–8%), and vagus nerve injury followed by hoarseness, dyspnea, and dysphagia because of left vocal cord paralysis. Delayed morbidity due to the device includes late infections or problems in wound healing; other more rare events are due to late injury of the nerve. Late complications due to nerve stimulation include delayed arrhythmias, laryngopharyngeal dysfunction (hoarseness, dyspnea, and coughing), obstructive sleep apnea, stimulation of phrenic nerve, tonsillar pain mimicking glossopharyngeal neuralgia, and vocal cord damage during prolonged endotracheal intubation. The laryngopharyngeal dysfunction occurs in about 66% of patients and is usually transitory and due to the stimulation of the inferior (recurrent) laryngeal nerve. A true late paralysis of the left vocal cord is often partial and rare (1–2.7%), and usually transitory, and may be caused by previous surgical trauma (i.e., damage of nerve fibers and/or of their blood supply) or to a supposed chronic denervation during stimulation. Surgery for complete removal or revision and replacement of the device is to be considered in cases of device malfunction (4–16.8%), failure of VNS therapy, intolerable side effects, or because of patient's specific request. As described in the literature, the surgical techniques of lead revision and replacement are two: sharp and blunt dissection of helical electrodes and replacement; and blunt dissection combined with ultrasharp low‐voltage cautery dissection. The incidence of left vocal cord palsy after vagus nerve stimulator replacement/revision is slightly higher than that of first implantation (4.9% vs. 3.8%). A de novo implantation in a naive segment of the left or right vagus nerve may be considered in specific cases; the use of the right vagus nerve is a rare exception that may be chosen with an acceptable result.